The impact of globalisation on regional identity: the example of Silesian identity - Sagan Radosław; Sitek Sławomir; Szajnowska-Wysocka Alicja (Bulletin of Geography. Socio-Economic Series, 2020)
Regional identity is a significant element of contemporary scientific discourse. It is justified in the era of progressing globalisation, which, by unifying traditional cultural patterns, forces regional communities to redefine their traditional values. Today, the Silesian identity is subject to such transformations. The distinctiveness thereof was shaped by many political, social and economic factors. Contemporarily, globalisation is a factor in socio-cultural transformations. The essence of the study of Silesian identity in the face of globalisation is to indicate the most important changes thereof reflected in the perception of the inhabitants of Katowice. The research goal is to analyse changes in the perception of globalisation and modern attitudes towards Silesian values (work and family).